Pengaruh Fraud Risk Factor dengan Pendekatan Fraud Hexagon Terhadap Kecurangan Laporan Keuangan: Penelitian - Regina Beatrix Takakobi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to investigate the influence of Financial Target, Ineffective Monitoring, and Change in Auditor, Board of Directors Replacement, Frequent Number of CEOs, and Collusion on the identification of financial statement fraud. Adopting a quantitative research approach, the study utilises data sourced from the official website of the Indonesia Stock Exchange (IDX). The research population comprises banking institutions listed on the IDX during the 2021–2022 period, with a total of 36 companies serving as the sample. All data were retrieved directly from the IDX’s official portal (www.idx.co.id). The analysis was conducted using SPSS version 26, applying logistic regression as the primary statistical method. The analytical process encompassed descriptive statistical evaluation, hypothesis testing through regression model feasibility assessment, model fit evaluation, determination coefficient analysis, and formulation of the final logistic regression model. The findings indicate that Financial Target (X1), Ineffective Monitoring (X2), Change in Auditor (X3), Frequent Number of CEOs (X5), and Collusion (X6) exert no significant impact on the detection of fraudulent financial reporting, whereas Board of Directors Replacement (X4) demonstrates a significant influence in uncovering such fraud.